Pemanfaatan Media Promosi dalam Pengembangan Usaha Mikro, Kecil dan Menengah (UMKM) Bilih 7 Muaro - Delvi Yanti; Deivy Andhika Permata; Lendrawati Lendrawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The activity aims to empower Micro, Small, and Medium Enterprises (MSMEs) named Bilih 7 Muaro through promoting online and offline media to expand the market network of its products. This activity was implemented in two steps: 1) identification of appropriate promotional activities to expand the marketing network of MSMEs of Bilih 7 Muaro products; and 2) carrying out promotional activities. The result of the activity was the promotion of the MSMEs of Bilih 7 Muaro product, which has been carried out offline and online. Offline promotional activities were carried out through the manufacture of signage and leaflets. The online promotional activities were carried out by making advertising videos uploaded on Youtube, making innovation chat videos (Ngovi) on Langgam TV, and promoting articles published in online mass media. In addition, the MSMEs of Bilih 7 Muaro carried out packaging renewal products to attract more attention from potential customers.